Oxidation of cofilin mediates T cell hyporesponsiveness under oxidative stress conditions - Klemke, Martin; Wabnitz, Guido H.; Funke, Faustina; Funk, Beate; Kirchgessner, Henning; Samstag, Yvonne (Immunity, 2008)
Oxidative stress leads to impaired T cell activation. A central integrator of T cell activation is the actin-remodelling protein cofilin. Cofilin is activated through dephosphorylation at Ser3. Activated cofilin enables actin dynamics through severing and depolymerization of F-actin. Binding of cofilin to actin is required for formation of the immune synapse and T cell activation. Here, we showed that oxidatively stressed human T cells were impaired in chemotaxis- and costimulation-induced F-actin modulation. Although cofilin was dephosphorylated, steady-state F-actin levels increased under oxidative stress conditions. Mass spectrometry revealed that cofilin itself was a target for oxidation. Cofilin oxidation induced formation of an intramolecular disulfide bridge and loss of its Ser3 phosphorylation. Importantly, dephosphorylated oxidized cofilin, although still able to bind to F-actin, did not mediate F-actin depolymerization. Impairing actin dynamics through oxidation of cofilin provides a molecular explanation for the T cell hyporesponsiveness caused by oxidative stress.
Gesehen am 16.07.2021